Strategi Pemasaran Toko Al-Karomah pada Masa Pandemi Covid-19 Ditinjau dari Marketing Syariah - Abraham Bayu Nugroho; Ahmad Fauzi (Universitas Islam Tribakti Lirboyo Kediri, 2022)
During the Covid 19 Pandemic, the impact was felt on the business world. This research focuses on the Marketing Strategy carried out by the Al-Karamah PP Store. Haji Ya'qub Lirboyo during the Covid-19 Pandemic in terms of Sharia Marketing. This research uses descriptive qualitative technique. Checking the validity of the data using the triangulation method, which is comparing findings using various data sources (al-Qur'an, hadith, books, journals, articles and so on) and various data collection methods (in-depth interviews, observation and documentation). As for the discussion by describing the data that has been obtained. The results of the study, namely: (1) The marketing strategy of the Al-Karamah PP Store. Haji Ya'qub Lirboyo, namely implementing segmentation, targeting, positioning strategies. In addition, it also implements the 4P Marketing Mix strategy and several other additional strategies. (2) Marketing Strategy for Al-Karamah PP Stores. Haji Ya'qub Lirboyo in the Covid-19 Pandemic Period was in accordance with sharia marketing, as evidenced by the suitability of the sharia marketing mix, the characteristics of a sharia marketer and the absence of behavior that deviated from religious norms in his marketing activities even during the Covid-19 pandemic. 19 at the moment.